Burnout and its Predictors among Undergraduate Medical Students: A Cross-sectional Study in Selected Medical Colleges in Bangladesh (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Prolong exposure or response to emotional and interpersonal stressor at the work place may result in burnout. Likewise, due to intense and demanding circumstances in the course of the curriculum of academic studies, medical students are vulnerable to develop burnout.Objective: To evaluate and compare the hematological and biochemical profiles of ringworm-infected patients with healthy controls at a tertiary care hospital.Methods: It was a cross-sectional study conducted from July 2023 to June 2024 with inclusion of conveniently selected 400 undergraduate medical students from three public and three private medical college in Bangladesh. Data were collected through face-to-face interview using a pre-tested semi-structured questionnaire.Results: The study revealed that studying in fifth year (OR 2.030, 95% CI=1.121-3.676), staying in mess (OR 10.690, 95% CI= 1.330-85.911), and with parent (OR 2.353, 95% CI=1.179-4.696), having inadequate (OR 1.936, 95% CI= 1.016-3.690), & no recreational facilities (OR 5.602, 95% CI= 2.005-15.654), no participation of games and sports (OR 1.746, 95% CI= 1.026-2.971), presence of no student welfare service (OR 1.625, 95% CI= 0.978-2.698), having disturbed sleep pattern (OR 2.401, 95% CI= 1.199- 4.807), use of internet for >6 hours/day (OR 2.589, 95% CI= 1.161-5.772) were important risk factors for the development of burn out in emotional exhaustion domain. In cynicism domain, respondents staying with parent (OR 2.584, 95% CI=1.266- 5.276), inadequate recreational facility (OR 1.820, 95% CI= 0.977-3.390), no recreation al facilities (OR 3.391, 95% CI= 1.242-9.255), use of internet for >6 hours/day (OR 2.694, 95% CI= 1.234-5.881) were important risk factors.Conclusion: The high prevalence of burnout suggests a pressing need for interventions targeted at these specific areas to enhance the well-being and academic performance of medical students.JAFMC Bangladesh, Vol 21, No 2 (December) 2025:3-10